Semitransparent Perovskite Solar Cells with Dielectric/Metal/Dielectric Top Electrodes - Xie, Xixi; Wu, Cuncun; Sun, Shuren; Xu, Xiaolong; Xu, Wanjin; Qin, Guogang; Xiao, Lixin (ENERGY TECHNOLOGY, 2020)
A semitransparent perovskite solar cell (PSC) with a dielectric/metal/dielectric (DMD) multilayer film as the top transparent electrode is investigated. Through adjusting the thickness and the deposition rate of Ag and WO3 layers, a transparent electrode with a low sheet resistance of 7 omega sq(-1) and high average visible transmittance (AVT) of 73% in the visible wavelength range of 400-800 nm is obtained. Using the resultant DMD film as the top transparent electrode and different bandgap perovskites of CH3NH3PbI3 (MAPbI(3)), CH(NH2)(2)PbI3 (FAPbI(3)), and FA(0.5)MA(0.38)Cs(0.12)PbI(2.04)Br(0.96) as the optical active layer, a solar cell with a device architecture of ITO/SnO2/perovskite/spiro-OMeTAD/MoO3/Ag/WO3 is fabricated. A series of efficient semitransparent PSCs with high transmittance are achieved.